PENGARUH SOCIAL MEDIA MARKETING, CELEBRITY ENDORSER, BRAND IMAGE, ELECTRONIC WORD OF MOUTH, DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH - Syntha Noviyana; Mella Sri Kencanawati; Reni Anggraini; Laras Ayu Irene Gayatri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
As the time goes by, the need for cosmetics are increasing. In their efforts to increase the purchase by the community, attention should be given to social media marketing, celebrity endorser, brand image, electronic word of mouth, and product innovations that Wardah did. The purpose of this research is to figure out how social media marketing, celebrity endorser, brand image, electronic word of mouth, and product innovations influence the purchase decision partially and simultaneously. The data used in this research was the primary data obtained from respondents were distributed online through google form. Samples were taken using non- probabilty sampling technique as many as 100 respondents. This research was conducted validity test, reliability test, classical assumption test, multiple linear regression analysis, partial t test, simultaneous F test, and analysis of the coefficient of determination (R2 ) using SPSS version 22 as a data processor. Based on the results of this research, it shows that partially celebrity endorser, brand image, and electronic word of mouth affect Wardah’s purchase decision, but social media marketing and product innovations don’t affect Wardah’s purchase decision. Meanwhile, social media marketing, celebrity endorser, brand image, electronic word of mouth, and product innovations simultaneously affects Wardah’s purchase decision.